A new, easy, and complete grammar of the Spanish language : a copious vocabulary, dialogues, &c., together with a commercial correspondence, fables, and prose and poetical extracts from the best authors ; which will be found of great utility to learners / compiled and arranged in the most perspicuous manner for the use of the author's commercial and military students by John Emm. Mordente, teacher of the Spanish language. - Mordente, John Emm. (John Emmanuel) (Tufts University. Tisch Library., 2015)
1 online resource (354 pages); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.